Rancang Bangun Sistem Keamanan Sepeda Motor Menggunakan Fingerprint Berbasis Arduino - bryan, Bryan Sham Rante Tandung (Universitas Muhammadiyah Riau, 2024)
This research is motivated by the existing security system in motorcycles that still considered to be not secure enough due to the use of conventional keys, which are relatively easy to be bypassed. The purpose of this research is to design and implement a motorcycle security system using a fingerprint-based Arduino. The research was conducted at a motorcycle workshop located at Jln. Tandipau IV, Sakti Village, Bua Sub-district, and lasted for 3 months. Qualitative data was collected, consisting of text-based information and non-numeric data obtained through interviews and literature review. Based on the observations made by the researcher, the fingerprint system works effectively when the fingerprint is dry. It responds slowly or may not respond at all if the fingerprint is wet, oily, dusty, or injured. The response time for fingerprint recognition when placing a fingerprint on the sensor takes 1 to 2 seconds.